User Satisfaction to Continuous Usage on QRIS Payment: Role of QRIS Contactless Payment Quality - Wicaksono, Ardian Oktavianto; Yuniawan, Fahmi Fauzi; Dirgantara, I Made Bayu (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2024)
This research aims to develop and evaluate an empirical model of the role of QRIS (Quick Response Code Indonesian Standard) Contactless Payment Quality, including Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Service Security (SS), in shaping User Satisfaction (US) and Continuous Usage (CU) among QRIS payment users in Central Java. The empirical model is built based on the Technology Acceptance Model (TAM) and existing literature on Contactless Payment Quality. For this purpose, an online survey was conducted with approximately 232 QRIS payment users aged 17 and above, and the data were analyzed using the Structural Equation Modeling (SEM) approach with the SmartPLS program. The study found that PEOU significantly influences PU. Additionally, the three components of Contactless Payment Quality (PEOU, PU, and SS) jointly determine US, and both US and SS together impact CU. Furthermore, this research demonstrates that US truly mediates the relationship between PEOU, PU, and SS with CU. Therefore, the findings contribute to the development of a holistic TAM and Contactless Payment Quality framework by providing a comprehensive model of antecedents and consequences of user satisfaction for QRIS payment users. The study also offers valuable insights for managers of companies managing QRIS systems.